2017
DOI: 10.3847/1538-4357/aa6ea9
|View full text |Cite
|
Sign up to set email alerts
|

Radii and Mass-loss Rates of Type IIb Supernova Progenitors

Abstract: Several Type IIb supernovae (SNe IIb) have been extensively studied, both in terms of the progenitor radius and the mass-loss rate in the final centuries before the explosion. While the sample is still limited, evidence has been accumulating that the final mass-loss rate tends to be larger for a more extended progenitor, with the difference exceeding an order of magnitude between the more and less extended progenitors. The high mass-loss rates inferred for the more extended progenitors are not readily explaine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 48 publications
11
57
0
Order By: Relevance
“…, when averaged over the final 1000 years before the SN explosion (Ouchi & Maeda 2017), which is comparable to that inferred from the radio observations for SN 2001ig (Ryder et al 2004). The CSM produced by the binary interaction could be the cause of the observed He II λ4686 feature discussed in Section 3.2.…”
Section: Binary Evolutionary Channel For the Sn 2001ig Progenitorsupporting
confidence: 82%
See 1 more Smart Citation
“…, when averaged over the final 1000 years before the SN explosion (Ouchi & Maeda 2017), which is comparable to that inferred from the radio observations for SN 2001ig (Ryder et al 2004). The CSM produced by the binary interaction could be the cause of the observed He II λ4686 feature discussed in Section 3.2.…”
Section: Binary Evolutionary Channel For the Sn 2001ig Progenitorsupporting
confidence: 82%
“…This particular BPASS model terminates with a primary core mass of ∼3.5 M e and with ∼0.04M e of H remaining. These numbers are quite similar to those yielded by the independent binary evolution models of Ouchi & Maeda (2017) for a secondary-to-primary mass ratio of 0.6<q<0.8, initial orbital period 200<P<600 days, and a low efficiency ( f≈0) of mass accretion from the primary onto the secondary. The blue loop in Figure 3 is similar to that seen in the models of Yoon et al (2017) for TypeIIb interacting binary progenitors with periods of a few hundred days, and masses closer to 10M e than 20M e .…”
Section: Photometric Properties Of the Companionsupporting
confidence: 81%
“…Götberg et al 2017Götberg et al , 2018. At low metallicity, Yoon et al (2010Yoon et al ( , 2017, Claeys et al (2011), andOuchi &Maeda (2017) show that the amount of hydrogen left at the surface of the donor star is a function of the initial orbital separation. In appendix C, we demonstrate that, for case B mass transfer, our general findings are robust against variations of the orbital period at low metallicity.…”
Section: Uncertaintiesmentioning
confidence: 99%
“…Note that type II objects can also exhibit enhanced pre-SNe mass-loss rates above 10 −3 M yr −1 (e.g. Das & Ray 2017;Arcavi et al 2017), and other studies have shown that such high mass-loss rates are not so rare among type IIb SNe (Fuller 2017;Ouchi & Maeda 2017). It is then reasonable to expect ∼1 to 2 cc-SNe withṀ > 10 −4 M yr −1 occurring per year, within a radius of 18 Mpc, whatever the sub-type.…”
Section: Prospects For Future Observationsmentioning
confidence: 97%